2020
DOI: 10.1186/s40621-020-00278-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to longer length of stay in Aboriginal and Torres Strait Islander children hospitalised for burn injury

Abstract: Background Aboriginal and Torres Strait Islander children have higher incidence, severity and hospital length of stay for their acute burn injuries than other Australian children. We examined factors contributing to longer length of stay for Aboriginal and Torres Strait Islander children with an acute burn injury. Methods Burns Registry of Australia and New Zealand admissions of children < 16 years of age between October 2009 and July 2018 were analysed. Descriptive statistics explored patient and injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
1
13
0
1
Order By: Relevance
“…Third, the parents preferred to discharge until the wound healed. In addition, the median LOS was 15 days (IQR: 8–25 days), which approximated the findings of existing studies ( 1 , 24 , 41 , 51 , 52 ). Analogous to cost, according to research results, LOS was associated with the etiology, TBSA, etc.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Third, the parents preferred to discharge until the wound healed. In addition, the median LOS was 15 days (IQR: 8–25 days), which approximated the findings of existing studies ( 1 , 24 , 41 , 51 , 52 ). Analogous to cost, according to research results, LOS was associated with the etiology, TBSA, etc.…”
Section: Discussionsupporting
confidence: 83%
“…Based on the investigation and analysis, publicity and education on burn prevention should be performed individually according to age ( 40 ). Preschoolers should be provided with extensive safety training regarding burn prevention, and guardians' awareness of prevention must be consistently reinforced to deepen and consolidate prevention knowledge ( 41 ). By sharing educational materials with guardians, preschool teachers, community workers, and rural committee members can alert them to prevent burns among school-age children.…”
Section: Discussionmentioning
confidence: 99%
“…This feature is rather essential, especially for victims admitted to burns centers from remote areas. Since the results of previous studies have shown that rural victims suffer more severe burns with greater complications and longer hospital stays compared to city dwellers [ 17 20 ], this group of victims have a greater need for rehabilitation measures. Meanwhile, they often leave the medical and rehabilitation process half-way through due to their long geographical distance from rehabilitation and medical centers and poor socioeconomic status and thus develop undesirable burns complications, such as deformity and several contractures, after a short while.…”
Section: Introductionmentioning
confidence: 99%
“…Chez l'enfant, les liquides chauds en sont la cause dans près de 75% des cas (Peck, 2011;Gülhan et al, 2019;Santiso et al, 2020). La gravité d'une brûlure est définie selon la surface corporelle brûlée (SCB), la profondeur, la localisation, le terrain (âge et antécédents) et l'existence de lésions associées (lésions pulmonaires par inhalation ou autres traumatismes) (Wassermann, 2002;Ryder et al, 2020;Zhang et al, 2020).…”
Section: Introductionunclassified